A hybrid lexicon-based and neural approach for explainable polarity detection. Issue 5 (September 2022) - Polignano, Marco; Basile, Valerio; Basile, Pierpaolo; Gabrieli, Giuliano; Vassallo, Marco; Bosco, Cristina
Abstract: In this work, we propose BERT-WMAL, a hybrid model that brings together information coming from data through the recent transformer deep learning model and those obtained from a polarized lexicon. The result is a model for sentence polarity that manages to have performances comparable with those at the state-of-the-art, but with the advantage of being able to provide the end-user with an explanation regarding the most important terms involved with the provided prediction. The model has been evaluated on three polarity detection Italian dataset, i.e., SENTIPOLC, AGRITREND and ABSITA. While the first contains 7, 410 tweets released for training and 2, 000 for testing, the second and the third respectively include 1, 000 tweets without splitting, and 2, 365 reviews for training, 1, 171 for testing. The use of lexicon-based information proves to be effective in terms of the F1 measure since it shows an improvement of F1 score on all the observed dataset: from 0.664 to 0.669 (i.e, 0.772%) on AGRITREND, from 0.728 to 0.734 (i.e., 0.854%) on SENTIPOLC and from 0.904 to 0.921 (i.e, 1.873%) on ABSITA. The usefulness of this model not only depends on its effectiveness in terms of the F1 measure, but also on its ability to generate predictions that are more explainable and especially convincing for the end-users. We evaluated this aspect through a user study involving four native Italian speakers, each evaluating 64 sentences with associated explanations. The results demonstrate the validity of this approach based on a combination of weights of attention extracted from the deep learning model and the linguistic knowledge stored in the WMAL lexicon. These considerations allow us to regard the approach provided in this paper as a promising starting point for further works in this research area. Highlights: Definition of an affective lexicon for the Italian language, WMAL. Definition of a hybrid lexicon-deep learning classification model. Definition of an explanation strategy for justifying the classifications obtained.